24/7. Late Capitalism and the Ends of Sleep (an excerpt) - Jonathan Crary (Journal of Economic Sociology, 2021)
24/7: Late Capitalism and the Ends of Sleep explores some of the ruinous consequences of the expansion of non-stop processes of twenty-first-century capitalism. The marketplace now operates around the clock, pushing us into constant activity and eroding forms of community and political expression, damaging the fabric of everyday life. In his book, Crary examines how this interminable non-time blurs any separation between an intensified, ubiquitous consumerism and emerging strategies of control and surveillance. He describes the ongoing management of individual attentiveness and the impairment of perception within the compulsory routines of our contemporary technological culture. At the same time, he shows that human sleep—a restorative withdrawal that is intrinsically incompatible with 24/7 capitalism—points to other more formidable and collective refusals of world-destroying patterns of growth and accumulation. The Journal of Economic Sociology will publish the first chapter of this book, which engages in a discussion of the reasons for sleep erosion and its connection to the dynamics of modern capitalism. Crary also alludes to the main threats of the 24/7 world and the possible human consequences.